Analysis of Managerial Innovation in UHT Milk Company - Roland YH Silitonga; Marla Setiawati; Theodorus Gratianus (Logistic and Operation Management Research (LOMR), 2022)
The study measured managerial innovation and its critical success factors of a Food & Beverages Company in Indonesia. To measure the level of managerial innovation of the company, we used two types of instruments. The first were questionnaires, using the employees as the respondents. The second was observation. The executives of the company performed it. To identify the critical success factors, we used questionnaires to check the perceptions of customers. The result of innovation level in the X company is 57%. The critical success factors from the creation element are values and organizations, and success factors from the deployment element are licensing, distribution, marketing, and launch timing.